Quantitatively detecting Candida albicans enolase1 with a one-step double monoclonal antibody sandwich ELISA assay - Piao, Jingzi; Li, Ning; Zhang, Lina; Meng, Hanbing; Sun, Qingqing; He, Zhengxin (Frontiers in Microbiology, 2023)
Invasive candidiasis (IC) is a severe concern to hospitalized patients, particularly those who are critically sick, however dealing with this disease is challenging due to a lack of effective laboratory diagnostic techniques. We developed a one-step double antibody sandwich enzyme-linked immunosorbent assay (DAS-ELISA) using a pair of specific monoclonal antibodies (mAbs) for the quantitative detection of Candida albicans enolase1 (CaEno1), an important diagnostic biomarker for IC. Diagnostic efficiency of the DAS-ELISA was evaluated using a rabbit model of systemic candidiasis and compared with other assays. The method validation results demonstrated that the developed method was sensitive, reliable, and feasible. The findings of the rabbit model plasma analysis revealed that diagnostic efficiency of the CaEno1 detection assay was comparable to that of the (1, 3)-β-D-glucan detection and superior to that of blood culture. CaEno1 is present in the blood of infected rabbits for a short period of time and at low levels, and the combination of CaEno1 antigen and IgG antibodies detection could aid to increase diagnostic efficiency. To improve the clinical applicability of CaEno1 detection in the future, efforts should be made to increase the detection limit of the test by technical developments and to optimize the protocol for clinical serial determinations.